THE FRAGILE SELF: UNRAVELING THE COMPLEX WEB OF FACTORS DRIVING ADOLESCENT IDENTITY INSECURITY - Qibtiya, Fairuzza Nur; Mubarak, Nisrina Tazkiya; Setiyowati, Ninik (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to investigate the contributing factors to identity insecurity among adolescents in the context of rapid digital development and intense social interaction. Method: A Systematic Literature Review (SLR) approach was employed by analyzing nine peer-reviewed articles published between 2019 and 2025, focusing on psychological theories, social dynamics, and the influence of social media. Results: The findings reveal that excessive use of social media, a strong tendency toward social comparison, low self-esteem, feelings of loneliness, and external social pressures significantly contribute to identity insecurity in adolescents. These factors disrupt the formation of a stable self-concept, especially in environments shaped by digital idealization and societal expectations. Novelty: This study offers a comprehensive synthesis of interdisciplinary perspectives, integrating psychological and sociocultural insights to enhance understanding of adolescent identity development in the digital era. The research emphasizes the urgency of targeted digital literacy programs and personalized counseling interventions to mitigate identity insecurity risks.